2022
DOI: 10.37989/gumussagbil.1001225
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship between Disaster Preparedness and Psychological Resilience in Emergency Aid and Disaster Management Students

Abstract: In this study, the relationship between the disaster preparedness belief status and psychological resilience of undergraduate students studying in the field of Emergency Aid and Disaster Management was examined. The research was designed in the correlational model. The universe of the study consists of 2430 undergraduate students studying in the field of Emergency Aid and Disaster Management in Turkey. The convenient sampling method, one of the non-random sampling methods, was used as a sample in the study. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Karakış (2019), in their study examining the disaster preparedness and psychological resilience of nurses working in public hospitals, they concluded that as the disaster preparedness perceptions of nurses increase, their psychological resilience also decreases (Karakış, 2019). Demirbilek and Gökkaya (2022), in their study investigating the relationship between disaster preparedness and psychological resilience of students, found that as disaster preparedness proficiency increases, students' resilience also increases. In his study (Demirbilek & Gökkaya, 2022), Karakış (2019), determined that as the psychological resilience of nurses' increases, their perception of preparedness for disasters also increases.…”
Section: Nurses' Perceptions Of Disaster Preparedness and Psychologic...mentioning
confidence: 99%
See 4 more Smart Citations
“…Karakış (2019), in their study examining the disaster preparedness and psychological resilience of nurses working in public hospitals, they concluded that as the disaster preparedness perceptions of nurses increase, their psychological resilience also decreases (Karakış, 2019). Demirbilek and Gökkaya (2022), in their study investigating the relationship between disaster preparedness and psychological resilience of students, found that as disaster preparedness proficiency increases, students' resilience also increases. In his study (Demirbilek & Gökkaya, 2022), Karakış (2019), determined that as the psychological resilience of nurses' increases, their perception of preparedness for disasters also increases.…”
Section: Nurses' Perceptions Of Disaster Preparedness and Psychologic...mentioning
confidence: 99%
“…Demirbilek and Gökkaya (2022), in their study investigating the relationship between disaster preparedness and psychological resilience of students, found that as disaster preparedness proficiency increases, students' resilience also increases. In his study (Demirbilek & Gökkaya, 2022), Karakış (2019), determined that as the psychological resilience of nurses' increases, their perception of preparedness for disasters also increases. Hong et al (2022), emphasized that there is a need for interventions to improve the disaster competence and psychological well-being of public health nurses.…”
Section: Nurses' Perceptions Of Disaster Preparedness and Psychologic...mentioning
confidence: 99%
See 3 more Smart Citations